Consumer insights via ethnography mengungkap yang tidak pernah terungkap Amalia E. Maulana ; editor, Audina Furi Nirukti, Daniel P.Purba - MAULANA, Amalia E; Nirukti, Audina Furi Purba, Daniel P (2009)
185 hlm ilus 23 cm